VD_FINDINFO HC / 2014 / 884 vom 18. September 2014 - VD Tribunal cantonal (2014)
DIVORCE, GARDE ALTERNÉE, OBLIGATION D'ENTRETIEN, MOTIVATION DE LA DEMANDE | 125 al. 1 CC, 133 CC, 276 CC, 285 al. 1 CC, 308 al. 2 CPC (CH), 311 al. 1 CPC (CH)